2022
DOI: 10.3389/fpls.2022.1012939
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic identification and molecular marker development of a novel wheat-Leymus mollis 4Ns(4D) alien disomic substitution line with resistance to stripe rust and Fusarium head blight

Abstract: Leymus mollis (Trin.) Pilg. (2n = 4x = 28, NsNsXmXm) potentially harbours useful genes that might contribute to the improvement of wheat. We describe M862 as a novel wheat-L. mollis alien disomic substitution line from a cross between wheat cv. 7182 and octoploid Tritileymus M47. Cytological observations indicate that M862 has a chromosome constitution of 2n = 42 = 21II. Two 4D chromosomes of wheat substituted by two L. mollis Ns chromosomes were observed, using the GISH and ND-FISH analyses. Molecular marker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…5c1). The standard FISH idiogram of common wheat was referenced to Tang et al [ 34 ] and Du et al [ 44 ]. The pattern of probes showed that the 6D chromosomes in D88-2a had normal FISH signals as it in the parent 7182, and the additional P. huashanica 6Ns chromosomes had no hybridization signals as it in P. huashanica by using the probe set of pSc119.2 and pTa535-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5c1). The standard FISH idiogram of common wheat was referenced to Tang et al [ 34 ] and Du et al [ 44 ]. The pattern of probes showed that the 6D chromosomes in D88-2a had normal FISH signals as it in the parent 7182, and the additional P. huashanica 6Ns chromosomes had no hybridization signals as it in P. huashanica by using the probe set of pSc119.2 and pTa535-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a wheat SNP array was used to analyse wheat-alien substitution and translocation lines because the lost wheat chromosomes caused a large number of deletions in SNP loci [ 44 ]. This study found that the 15 K SNP array could also accurately identify the homoeologous groups of alien chromosomes in addition lines, which might be because the genotype of SNPs on the target homologous group chromosomes were affected by alien chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Developing accurate markers using transcriptome sequencing technology is more effective. Compared with traditional methods, modern sequencing technology could provide a precise and rich source for developing specific markers [ 52 ]. For example, specific markers on the Dasypyrum villosum chromosome were designed via genotyping-by-sequencing (GBS) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%